ANALISIS CACAT PADA PEMASANGAN GASKET DI LINI ASSEMBLY DENGAN PENDEKATAN DMAIC SIX SIGMA - Nirfison Nirfison; Rahman Soesilo (Jurnal Taguchi : Jurnal Ilmiah Teknik dan Manajemen Industri, 2022)
In the production process, defects or defects are difficult to avoid. The same thing happens in the process of installing gaskets on the refrigerator door. The gasket itself serves as an insulator and also as a door adhesive with the refrigerator cabinet. Inside the gasket is a magnetic metal plate. The defect that occurs is the gap between the door and the refrigerator cabinet. In other words, the gasket does not sit properly in the refrigerator cabinet, causing a gap called a defect gap. This defect gap greatly affects the performance of the refrigerator, because cold air from the refrigerator will come out through the gap between the gasket and the refrigerator cabinet which can cause the cooling process of the refrigerator to be disrupted. To reduce these defects, further analysis is needed to find the causes and at the same time alternative improvements. The method used in this study is the DMAIC six sigma approach